ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI RISIKO INVESTASI SAHAM PADA GENERASI Z DI INDONESIA - Ika Lista Fadila; Fatimah Nasywa Azhar; Dea Amelia Putri; Gusganda Suria Manda (LPPM Politeknik Pratama, 2025)
This study aims to analyze the factors influencing the risk perception of stock investments among Generation Z in Indonesia. The research method used is quantitative, employing a survey approach through questionnaires. The analytical technique applied is multiple linear regression. The results of the study indicate that financial literacy, investment experience, and social influence significantly impact risk perception. These findings have important implications for financial education providers and capital market institutions.